Perancangan Media Pembelajaran Menggunakan Android pada Mata Pelajaran Dasar-dasar Algoritma dan Pemrograman untuk Siswa Kelas X TKJ SMKN 1 Baso - Saputra, Wanda Febrian; Sesmiarni, Zulfani; M, Iswantir; Charles, Charles (Indonesian Research Journal on Education, 2023)
Prior to this, learning the basics of algorithms and programming for class X TKJ SMK N 1 BASO has not used varied learning media so that students lack motivation in learning. This study aims to develop learning media using android in the lessons of the basics of algorithms and programming to and determine the feasibility of the developed learning media. This study uses the ADDIE development method, namely: 1. Analyze (Analysis), 2. Disign (design design), 3. Developme (development), 4. Implementation (implementation), 5. Evaluation (evaluation). This research was conducted at SMK N 1 BASO in early January to late January 2021 and to determine the feasibility of this product. From the product test that the author did, he obtained a validity test with an average value of 0.90 which is very valid, the author's practicality test got an average of 1.0 with a very high category, and the author's effectiveness test got an average value of 0.98, based on the results of this product test, can help students, teachers or lecturers who will conduct research in the field of education so that research can be continued to see the success of using this learning media for students and prospective teachers and teachers can develop material from this design that has been designed.